2013
DOI: 10.1089/pho.2013.3569
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Er,Cr:YSGG Laser Irradiation on the Push-Out Bond Strength of RealSeal Self-Etch Sealer

Abstract: Objective: The aim of this study was to evaluate the effect of an erbium, chromium: yttrium-scandium-galliumgarnet (Er,Cr:YSGG) laser on the push-out bond strength of RealSeal Self-Etch (SE) sealer. Background data: Various methods are used for smear layer removal in endodontics, such as the application of Er,Cr:YSGG lasers. This laser system may influence the bond strength of resin-based sealers. Methods: Sixty single-rooted extracted teeth were selected. After root canal preparation, samples were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
8
0
3
Order By: Relevance
“…According to Esteves-Oliveira et al (17), these wavelengths increase root dentin permeability, therefore, the demineralizing effect of the EDTA used could also be increased, with deeper mineral removal. Corroborating with these results, previous studies already observed the positive effect of different lasers systems on retention of resin-based root canal sealers (24,25). Recently, Lopes et al (26) observed that high power lasers combined to NaOCl and EDTA change the root dentin inorganic/organic ratio and that could be a contributive factor to sealers retention to root dentin.…”
Section: Discussionmentioning
confidence: 52%
“…According to Esteves-Oliveira et al (17), these wavelengths increase root dentin permeability, therefore, the demineralizing effect of the EDTA used could also be increased, with deeper mineral removal. Corroborating with these results, previous studies already observed the positive effect of different lasers systems on retention of resin-based root canal sealers (24,25). Recently, Lopes et al (26) observed that high power lasers combined to NaOCl and EDTA change the root dentin inorganic/organic ratio and that could be a contributive factor to sealers retention to root dentin.…”
Section: Discussionmentioning
confidence: 52%
“…In group 2, the canals were filled with distilled water and received 2.78 lm Er,Cr:YSGG laser irradiation (Waterlase Millenium, Biolase Technology, San Clement, CA), with a 320 lm diameter radial firing tip (RFT3 Endolase, Biolase Technology, Inc; calibration factor of 0.85) and the following parameters: panel output power of 1.5 W, pulse duration of 140 ls, pulse frequency of 20 Hz, and 15% water pressure to 15% air pressure ratio. 13,14 The energy per pulse of 42 mJ and energy density of 5.25 J/cm 2 were calculated. The laser tip was inserted into each canal at the working length and moved continuously in a circular motion from the apex to the crown at a speed of 2 mm/sec.…”
Section: Methodsmentioning
confidence: 99%
“…This outcome is consistent with the hypotheses generated in other studies. 13 In contrast to its efficacy regarding smear layer removal, the Er,Cr:YSGG laser failed to effectively remove debris as compared with EDTA and NaOCl ( Table 2). Previous studies have shown better results for debris removal using laseractivated irrigation with Er,Cr:YSGG lasers, and Er:YAG lasers compared with passive ultrasonic irrigation techniques.…”
Section: Effect Of Ercr:ysgg On Smear Layer and Debris 529mentioning
confidence: 97%
“…O laser pode ser utilizado como auxílio, para melhorar não só a limpeza e a desinfecção, mas também o vedamento do sistema de canais radiculares no momento da obturação, apresentando resultados promissores, uma vez que promove modificações morfológicas na parede dentinária e na camada de smear, (TAKEDA et al, 1998;1999;YAMAZAKI et al, 2001;SANTOS et al, 2005;COSTA-RIBEIRO et al, 2007;MOHAMMADI, 2009;VIOLICH;CHANDLER, 2010;SILVA et al, 2010), redução microbiana (BELIKOV et al, 1995;GUTKNECHT et al, 2004;VEZZANI et al, 2006;YASUDA et al, 2010;YAVARI et al 2010;MEIRE et al, 2012), selamento do forame apical (WEICHMAN; JOHNSON, 1971;NEIBURGER, 1992;GEKELMAN et al, 2002;GARIP et al, 2011;MARQUES et al, 2011) e alteração da permeabilidade dentinária (BRUGNERA-JUNIOR et al, 2003;ARANHA et al, 2005;ESTEVES-OLIVEIRA et al, 2010;SILVA et al, 2010) (VERGAUWEN et al, 2014), conduz uma mistura de água e vapor através de uma fibra ótica coberta por safira, trabalhando de modo pulsado, com duração de 140 a 200 µs, taxa de repetição de 5 a 100 Hz, podendo variar a potência de 0 até 6 W. Possui comprimento de onda de 2,79 μm, que, ao ser absorvido pela água e hidroxiapatita, causa micro explosões e remoção do tecido alvo por ablação (EHSANI et al, 2013).…”
Section: Introductionunclassified
“…A ablação é um processo de remoção de tecido, onde os fótons são absorvidos causando um rápido aumento de temperatura e da pressão de água intersticial, o que leva à ruptura do tecido adjacente, removendo-o juntamente com o vapor de água formado. Um dos diferenciais do laser Er,Cr:YSGG é a possibilidade de controle de ar e água durante a irradiação, além de possuir pontas específicas flexíveis para uso endodôntico, as quais podem ser inseridas até o comprimento de trabalho por possuir diâmetro compatível com o diâmetro interno do canal radicular (EKWORAPOJ; SIDHU; MCCABE, 2007;SCHOOP et al, 2009;EHSANI et al, 2013;VERGAUWEN et al, 2014;KIRMALI et al, 2014).…”
Section: Introductionunclassified